Fuzzy arithmetical modeling of a steam turbine and a boiler system - Wan Mohamad, Wan Munirah; Ahmad, Tahir; Ab Karim, Niki Anis; Ashaari, Azmirul (Mathematical Modelling and Analysis, 2018)
The steam turbine and a boiler are important components of a power generation plant. Improved efficiency of a power plant leads to increase of energy production and less waste. In this paper, a model of the power plant as a multivariable system using fuzzy arithmetic which is based on the Transformation Method (TM) is presented. The analytical solution is used to evaluate the state space model. The TM is then used to quantify the inuence of each parameter and their gain factors are calculated to allow estimation of relative measures of uncertainty. The method is applied to a boiler and a steam turbine systems for simulation, analysis and indication of TM’s efficiency. The efficiency of TM is presented in this paper.